If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying xy + 2 = 9 Reorder the terms: 2 + xy = 9 Solving 2 + xy = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + xy = 9 + -2 Combine like terms: 2 + -2 = 0 0 + xy = 9 + -2 xy = 9 + -2 Combine like terms: 9 + -2 = 7 xy = 7 Divide each side by 'y'. x = 7y-1 Simplifying x = 7y-1
| -y=3x+5 | | 1+2.3x-5.4x+9.2=76 | | 9x^2-11x+4=8x^2+20 | | [6+11]*8= | | 9+10x-12x=20 | | 1607.6=1.8C+32 | | 3(b+13)-12=45 | | 1.1+2.4f=8.3 | | 2s-4+3s=2s-1 | | 9x-71+8x=133 | | 0.70x+0.20(400-x)=0.60(400) | | 8y+4=7y | | 5x+4y+19=0 | | 27x=1377 | | -(4x-5)-(4x-6)+8=-4(x-1)-(8x+4)+3 | | 5x=0.125 | | 4x-5y-19=0 | | 7y+2x=14 | | 7x+13=6x+7 | | 2n-(3n+2)=6 | | 4x-5y+19=0 | | k^2-18k+37=8 | | 9x-6x+x=-3 | | X^2+8xy-65y= | | 5x-4y-19=0 | | 0.70x+0.20(100-x)=0.60(100) | | -7x=4x+33 | | 9(2x+4)=-3(x+2) | | X+119=321 | | 3y=12+2y | | 39=12+2y | | 7(-7)-4(-2)=29 |